2015
DOI: 10.3390/w7095155
|View full text |Cite
|
Sign up to set email alerts
|

Flood-Runoff in Semi-Arid and Sub-Humid Regions, a Case Study: A Simulation of Jianghe Watershed in Northern China

Abstract: This paper presents a modeling application of surface runoff using the Hydrologic Modelling System (HEC-HMS). A case study was carried out for the Jianghe watershed, a typical semi-arid and sub-humid geo-climatic region in northern China. Two modeling schemes using different descriptive sub-mechanism models provided by HEC-HMS for runoff volume, direct runoff and routing (channel flow) were investigated. The modeling results were compared with historical observation data. This work shows that HEC-HMS can be a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 15 publications
2
38
0
Order By: Relevance
“…Among the 11 infiltration methods of the HEC‐HMS model, ‘SCS‐CN’ (USDA‐SCS, ), ‘Green‐Ampt’ (Rawls et al , ) and ‘Initial and Constant’ methods (USDA‐NRCS, ) were chosen. More details about equations simulating infiltration losses can be found for ‘SCS‐CN’ and ‘Initial and Constant’ methods in the HEC‐HMS technical manual (Feldman, ), and for ‘Green‐Ampt’ method in the papers of Jin et al () as well as Ficklin and Zhang ().…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the 11 infiltration methods of the HEC‐HMS model, ‘SCS‐CN’ (USDA‐SCS, ), ‘Green‐Ampt’ (Rawls et al , ) and ‘Initial and Constant’ methods (USDA‐NRCS, ) were chosen. More details about equations simulating infiltration losses can be found for ‘SCS‐CN’ and ‘Initial and Constant’ methods in the HEC‐HMS technical manual (Feldman, ), and for ‘Green‐Ampt’ method in the papers of Jin et al () as well as Ficklin and Zhang ().…”
Section: Methodsmentioning
confidence: 99%
“…The three infiltration methods analysed in this study were selected, because the required input parameters were available or could be easily estimated by the experimental database of the studied basin. Moreover, previous studies have shown that the ‘Initial and Constant’ and ‘SCS‐CN’ methods have been used successfully to model flooding (Jin et al , ), being conceptually simple models. The more complex ‘Green‐Ampt’ method was applied to assess its performance in the present case of scarcity of soil data, but availability of sub‐daily precipitations.…”
Section: Methodsmentioning
confidence: 99%
“…HEC-HMS is one of those models significantly used in different parts of the world for estimating runoff by considering different modelling approaches, in which both lumped and distributed modelling approaches and concepts are embedded in the programme [16,17].HEC-HMS is hydrological modelling software developed by the US Army Corps of Engineers Hydrologic Engineering Centre (HEC), which is designed to simulate the precipitation runoff processes within a wide range of geographic areas, such as large river basins and small urban or natural watersheds [17,18]. Because of its ability in the simulation of runoff both in short and long time events, ease to use, and use of common methods, HEC-HMS has become very popular and been adopted in many hydrological studiesin relation to the simulation of runoff volume in integrated water resources and watershed management projects and for estimating flood peaks in flood forecasting, irrespective of the size of the catchment [12,[18][19][20][21][22][23][24][25][26][27][28][29][30]. A special extension programme of the HEC-GeoHMS in ArcGIS has been applied in some of the studies and allowed researchers to generate relevant spatial data in relation to terrain characteristics which cloud be used as input data for HEC-HMS mode [2,12,21,[24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Because of its ability in the simulation of runoff both in short and long time events, ease to use, and use of common methods, HEC-HMS has become very popular and been adopted in many hydrological studiesin relation to the simulation of runoff volume in integrated water resources and watershed management projects and for estimating flood peaks in flood forecasting, irrespective of the size of the catchment [12,[18][19][20][21][22][23][24][25][26][27][28][29][30]. A special extension programme of the HEC-GeoHMS in ArcGIS has been applied in some of the studies and allowed researchers to generate relevant spatial data in relation to terrain characteristics which cloud be used as input data for HEC-HMS mode [2,12,21,[24][25][26][27][28][29][30]. After appropriate calibration and validation tasks in each selected loss, transform methods, and routing reaches in the HEC-HMS programme, reasonable and reliable simulation results of runoff volume and peak values were obtained as compared to observational data in all the studies.…”
Section: Introductionmentioning
confidence: 99%
“…This method describes the loss of precipitation by vegetation interception, depression storage, evaporation, evapotranspiration, and infiltration, and indicates whether runoff is generated. The SCS Water 2017, 9, 870 8 of 27 method calculates the precipitation excess as a function of cumulative rainfall, soil cover, land use, and antecedent moisture content [38,39]. The equation is expressed as follows:…”
Section: Rainfall Losses Calculationmentioning
confidence: 99%